Soil pH Range for Optimum Commercial Vegetable Production - Guodong Liu; Edward Hanlon (EDIS)
Soil pH affects nutrient bioavailability by controlling the chemical forms of nutrients. This 11-page fact sheet provides information about soil pH basics to commercial growers, county Extension agents, and college students specializing in vegetable production. Written by Guodong Liu and Edward Hanlon, and published by the UF Department of Horticultural Sciences, October 2012.